The knowledge Vee as a tool to foster students´ and teachers´ creativity - Chrobak, Ricardo; Beatriz Prieto, Ana (Anales de Psicología / Annals of Psychology, 2010)
There are numerous publications that address different ways of approaching the teaching process, taking into account different perspec-tives to understand the role of teachers and students, such as “teaching creatively”, “teaching for creativity”, “creative Teaching”, “creative Learn-ing”, etc. In all these cases a strong interaction between those involved in the teaching and learning process is recognized. In this work, we under-stand competent teaching as a means or method by which both parties involved (students and teachers) collaborates in order to achieve class-room practices that ensure creative learning. The aim of this work is primarily to further the study of the application of metacognitive tools during the teaching and learning process, focusing particularly on the knowledge or heuristic Vee (also called Gowin´s Vee, named after its creator). This use of the Vee will foster creative learning in the field of natural sciences. In order to verify this claim, we analyzed the educational experience of university professors who completed their mas-ter´s or a specialization degree program which focused on the teaching of Natural Sciences. All of them have used the knowledge Vee during their teaching practice